A Study on the Relationship Between Reading Habits and English Reading Comprehension of Tenth Grade Students of Broadcasting Deparment at Smk Negeri 2 Kupang in the Academic Year 2025/2026 - Yuliana Darlin Basri; Alexander H. Kabelen; Antonia Tefa (Indonesian Journal Publisher, 2026)
This study aimed to determine the relationship between students’ reading habits and their reading comprehension in English at Grade X Broadcasting Department of SMK Negeri 2 Kupang in the Academic Year 2025/2026. This study employed a descriptive qualitative method. The participants of the study were ten students of Grade X Broadcasting who were selected based on several criteria, including their reading habits, reading abilities, participation in classroom activities, and willingness to participate in the interview process. The data were collected through classroom observation and semi-structured interviews. The data were analyzed using Miles and Huberman’s interactive model, which consists of data reduction, data display, and conclusion drawing.The findings showed that students had different reading habits in terms of reading interest, reading frequency, types of reading materials, and reading strategies. The observation results indicated that students who were able to read texts fluently, clearly, and confidently generally demonstrated better comprehension of the texts. Meanwhile, students who experienced difficulties in reading also faced difficulties in understanding the content of the texts. The interview results revealed that students who read more frequently tended to have better vocabulary knowledge, used effective reading strategies, and found it easier to understand English texts. In contrast, students who rarely read reported difficulties related to limited vocabulary and lack of reading practice. Based on the observation and interview findings, the study concluded that there was a relationship between students’ reading habits and their reading comprehension in English.